Elementy interaktywne w systemach zdalnej edukacji - Dębska, Barbara; Kubacka, Agnieszka (The Interactive Elements in Distance Learning, 2005)
The project that has been carried out for the last two years in the State Higher School of Vocational Education in Krosno (PWSZ) is aimed at introducing elements of e-learning into the teaching of the subject entitled "Algorithms and data structures". The subject is taught to 1st year students. The didactic materials are collected in two databases: a static and a dynamic one. The static database includes sets of definitions, exercises and tests. The dynamic one includes programmes containing animations, simulations or interactive elements. Much attention was paid especially to the use of interactive elements in multimedial lessons devoted to sorting algorithms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 349-357